2003
DOI: 10.1186/cc2366
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sufficient nutrients are needed for critically ill patients to meet metabolic needs. Previous studies have shown that appropriate nutritional feeding during critical illness improves the success in weaning patients from mechanical ventilation and in reducing the length of hospitalization [1][2][3][4][5] Correspondence: Yi-Chia Huang, ych@csmu.edu.tw AF = appropriate feeding; APACHE = Acute Physiology and Chronic Health Evaluation; ICU = intensive care unit; MAC = mid-arm circumference; MEE = measured energy ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 30 publications
1
8
1
2
Order By: Relevance
“…Respiratory quotient fluctuates with feeding, nutritional status, and anaerobiosis (43, 44), factors not considered here. The unadjusted Harris-Benedict equation has been shown previously to be unreliable in predicting energy expenditure in critically ill patients (39), which in part may be due to variation in ventilator settings (15, 45, 46), metabolic stress (47, 48), and fasting status (44) in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory quotient fluctuates with feeding, nutritional status, and anaerobiosis (43, 44), factors not considered here. The unadjusted Harris-Benedict equation has been shown previously to be unreliable in predicting energy expenditure in critically ill patients (39), which in part may be due to variation in ventilator settings (15, 45, 46), metabolic stress (47, 48), and fasting status (44) in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…The patients included in the study were divided into three groups: underfed, who received less than 90% of the necessary nutrition; appropriate feeding, receiving nutrition with an error of plus or minus 10%; and overfed patients, who received more than 110% of the necessary. Following the study, a significant improvement in hemodynamic status was reported in patients whose nutrition was individualized and related to their needs, reducing both the time of mechanical ventilation and the time in the ICU [ 55 ].…”
Section: Reviewmentioning
confidence: 99%
“…No entanto, um aporte calórico adequado pode promover o desmame da VM em pacientes críticos, reduzindo o tempo de internação hospitalar e a ocorrência de infecções 10 .…”
Section: N T R O D U ç ã Ounclassified
“…No estudo realizado por Kan et al 10 , os pacientes que receberam uma alimentação inadequada para suprir a demanda energética dependeram por mais tempo da VM. O presente estudo não encontrou associação estatisticamente significativa entre o percentual de calorias administradas e os tempos de VM (r s =0,130; p=0,321), de permanência em UTI (r s =-0,117; p=0,372) e de internação hospitalar (r s =-0,152; p=0,246).…”
Section: I S C U S S ã Ounclassified